Empowering Mothers of Toddlers as an Effort to Reduce Stunting Rates in Surenlor Village - Azzahra, Erica Ardhana Fathimah; Wahyuni, Wiwik; Rizkita, Aden Dhana (Proceeding International Conference on Religion, Science and Education, 2024)
Stunting is the impact of malnutrition during the first thousand days of life. If they don’t get treatment early on, children with stunting can experience growth and development disturbances and continue into adulthood. Surenlor Village’s stunting rate decreased from 22.98% in 2019 to 13.17% in 2022. Despite the decrease, the percentage of stunting in Surenlor Village still needs special attention. One of the efforts to reduce the prevalence of stunting is by increasing the knowledge of mothers of babies and toddlers about how to prevent stunting. Seeing these problems, counseling was held about stunting prevention in Surenlor Village. Goal: to avoid stunting by increasing the knowledge of mothers of babies and toddlers about how to prevent stunting in Surenlor Village, Bendungan District, Trenggalek Regency. Method: the implementation method used is counseling to prevent stunting. Results and discussion: the impact of this counseling is there is an increase in the knowledge of mothers of infants and toddlers regarding stunting prevention before and after counseling activities. Conclusion: counseling activities regarding stunting prevention were well received, and the knowledge of mothers of babies and toddlers in Surenlor Village, Bendungan District, Trenggalek Regency was increased.